2021
DOI: 10.1007/s13164-021-00525-w
|View full text |Cite
|
Sign up to set email alerts
|

The Roots of Racial Categorization

Abstract: I examine the origins of ordinary racial thinking. In doing so, I argue against the thesis that it is the byproduct of a unique module (e.g. a folk-biology module). Instead, I defend a pluralistic thesis according to which different forms of racial thinking are driven by distinct mechanisms, each with their own etiology. I begin with the belief that visible features are diagnostic of race. I argue that the mechanisms responsible for face recognition have an important, albeit delimited, role to play in sustaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 110 publications
(111 reference statements)
0
5
0
Order By: Relevance
“…For instance, when people see a political or ideological opponent as belonging to the same racial group as them, they might place them relatively high up on the descriptive dimension, but relatively low down on the normative dimension. Moreover, if people tend to view traits such as intelligence and rationality as central to being human (in descriptive sense), they may view their political and ideological opponents as especially threatening because they perceive them as "entitative" groups who are highly capable of implementing their morally deviant values (see Phillips 2022bPhillips , 2022c. As I explain below, this is arguably how the Nazis tended to think of Jewish people: namely, as humans in the descriptive sense, with traits such as intelligence and rationality, but as subhumans in the normative sense, with traits such as evilness and criminality.…”
Section: Normative Dehumanization and Intergroup Hostilitymentioning
confidence: 99%
“…For instance, when people see a political or ideological opponent as belonging to the same racial group as them, they might place them relatively high up on the descriptive dimension, but relatively low down on the normative dimension. Moreover, if people tend to view traits such as intelligence and rationality as central to being human (in descriptive sense), they may view their political and ideological opponents as especially threatening because they perceive them as "entitative" groups who are highly capable of implementing their morally deviant values (see Phillips 2022bPhillips , 2022c. As I explain below, this is arguably how the Nazis tended to think of Jewish people: namely, as humans in the descriptive sense, with traits such as intelligence and rationality, but as subhumans in the normative sense, with traits such as evilness and criminality.…”
Section: Normative Dehumanization and Intergroup Hostilitymentioning
confidence: 99%
“…There is also evidence that applications of the folk concept GROUP are guided by attributions of shared intentionality. A number of studies have found that entitativity perceptionthe tendency to regard some aggregates of people as more "groupish" than others is mediated by judgments concerning shared intentionality (for some recent discussions, see Phillips, 2021a, b). For example, people's impression that an aggregate of individuals constitutes a genuine group is enhanced when they observe these individuals moving in synchrony Lakens & Stel, 2011;Wilson & Gos, 2019).…”
Section: Referencementioning
confidence: 99%
“…To illustrate, consider racial groups again. If the context is such that one is thinking about racial groups in dynamical terms, one's attention will be guided towards certain features (for further discussion, see Phillips, 2020). For example, perhaps one is thinking about tensions between the police force and the African American community.…”
Section: Top-down Salience Effectsmentioning
confidence: 99%
“…For our purposes, the key finding is that in one context, attention to the relevant features can cause people see racial groups as highly entitative; whereas, in a different context, in which attention is not drawn to the relevant features, the same racial groups are not processed as highly entitative (for further discussion, see Phillips, 2021).…”
Section: Entitativity Perception and Top-down Salience Effectsmentioning
confidence: 99%